2011
DOI: 10.3109/17477166.2011.575149
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference predicts increased cardiometabolic risk in normal weight adolescent males

Abstract: WC within BMI categories may identify those who have cardiometabolic disease risk factors despite having normal or overweight BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…A study among 359,387 European adults showed that the associations of waist circumference with risk of death were stronger among subjects with a lower BMI (4). Similarly, a study among 2,003 adolescents showed that males with a normal BMI and elevated waist circumference were more likely to have elevated levels of cardiovascular risk factors (23). We observed that the associations of higher abdominal fat mass measures with cardiovascular risk factors were stronger among obese children.…”
Section: Interpretation Of Main Findingssupporting
confidence: 48%
“…A study among 359,387 European adults showed that the associations of waist circumference with risk of death were stronger among subjects with a lower BMI (4). Similarly, a study among 2,003 adolescents showed that males with a normal BMI and elevated waist circumference were more likely to have elevated levels of cardiovascular risk factors (23). We observed that the associations of higher abdominal fat mass measures with cardiovascular risk factors were stronger among obese children.…”
Section: Interpretation Of Main Findingssupporting
confidence: 48%
“…Some authors 38,39 argue that measures of abdominal adiposity might be more useful predictors of cardiometabolic risk in non-obese adolescents, once excess abdominal adiposity could be missed if using a whole body measure such as BMI. There may also exist differences between sexes as Cartier et al 40 highlighted, although in adults, that CRP concentrations seem to be influenced to a greater extent by visceral adiposity in men, as opposed to subcutaneous adiposity in women.…”
Section: Discussionmentioning
confidence: 99%
“…According to Taylor et al, 39 youths have the WC equivalent of adult abdominal obesity at percentiles lower than the frequently used pediatric threshold of 90%. Besides, the WC cut-off values for pediatric ages have to be age and sex specific, so, a fixed cut-off point for WC not taking account of height might underestimate the relative amount of abdominal fat in short subjects and overestimate it in tall subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that people with abdominal obesity are more likely to have diabetes 21,22 and to be at increased risk for cardiovascular disease. 23,24 Also, as abdominal obesity in midlife may develop an elevated risk of diabetes in older age, it is an important factor in predicting diabetes. 25 It is important to note that abdominal obesity is just one of several factors that are associated with prediabetes.…”
Section: Discussionmentioning
confidence: 99%